Cannabis sativa and Skin Health: Dissecting the Role of Phytocannabinoids - Martinelli, Giulia; Magnavacca, Andrea; Fumagalli, Marco; DellʼAgli, Mario; Piazza, Stefano; Sangiovanni, Enrico (Planta Medica, 2021)
The use of Cannabis sativa is currently recognized to ease certain types of chronic pain, reduce chemotherapy-induced nausea, and improve anxiety. Nevertheless, few studies highlighted the therapeutic potential of C. sativa extracts and related phytocannabinoids for a variety of widespread skin disorders including acne, atopic dermatitis, psoriasis, pruritus, and pain. This review summarized the current evidence on the effects of phytocannabinoids at the cutaneous level through the collection of in vitro, in vivo, and clinical studies published on PubMed, Scopus, Embase, and Web of Science until October 2020. Phytocannabinoids have demonstrated potential anti-inflammatory, antioxidant, anti-aging, and anti-acne properties by various mechanisms involving either CB1/2-dependent and independent pathways. Not only classical immune cells, but also several skin-specific actors, such as keratinocytes, fibroblasts, melanocytes, and sebocytes, may represent a target for phytocannabinoids. Cannabidiol, the most investigated compound, revealed photoprotective, antioxidant, and anti-inflammatory mechanisms at the cutaneous level, while the possible impact on cell differentiation, especially in the case of psoriasis, would require further investigation. Animal models and pilot clinical studies supported the application of cannabidiol in inflammatory-based skin diseases. Also, one of the most promising applications of non-psychotropic phytocannabinoids is the treatment of seborrheic disorders, especially acne. In conclusion, the incomplete knowledge of the role of the endocannabinoid system in skin disorders emerged as an important limit for pharmacological investigations. Moreover, the limited studies conducted on C. sativa extracts suggested a higher potency than single phytocannabinoids, thus stimulating new research on phytocannabinoid interaction.
Keywords: Cannabis sativa; Cannabaceae; phytocannabinoids; skin diseases; acne; psoriasis; CBD